Characteristics of mechanical properties of sulphur cross-linked guayule and dandelion natural rubbers. Issue 80 (1st November 2017) - Junkong, P.; Cornish, K.; Ikeda, Y.
Abstract : Roles of non-rubber components in guayule and dandelion natural rubbers on the mechanical properties are firstly revealed by analysing the Mullins effect, dynamic mechanical properties and strain-induced crystallization from a new viewpoint. Abstract : Roles of non-rubber components in guayule and dandelion natural rubbers on the mechanical properties of each sulphur cross-linked rubber are revealed for the first time by analysing the Mullins effect, dynamic mechanical properties and strain-induced crystallization (SIC) from a new viewpoint, in comparison with sulphur cross-linked Hevea natural rubber (S-NR) and synthetic isoprene rubber (S-IR). Physically aggregated non-rubber components, particularly proteins, work as "natural reinforcing fillers". Higher-order structures of the physically aggregated non-rubber components in guayule (S-GR) and dandelion (S-DR) natural rubber matrices are proposed on the basis of their characteristic mechanical responses and SIC phenomena. Soft aggregates in S-GR accelerated the orientation of rubber chains and further development of SIC. The stronger physically aggregated non-rubber components, especially proteins in S-DR, accelerated SIC at the beginning of stretching, but impeded the orientation of rubber molecules with further stretching, resulting in the less development of SIC. This was also seen to a lesser degree in S-NR. The physical interaction of the aggregates of non-rubber components in dandelion natural rubber was suggested to be weaker than that in Hevea natural rubber. These phenomena could explain the characteristics of generated strain-induced crystallites during deformation in all samples, which clearly support the concept of "template crystallization" for SIC phenomena. SIC is a key parameter which should be considered in order to effectively utilize guayule and dandelion natural rubbers as alternatives for Hevea natural rubber in rubber industry.